Computational Optimization Using Spherical Geometric Modeling for Time-Domain Wave Propagation - Almeida, Dayalla M. P.; Paiva-da-Silva, Bruno V.; Rodrigues, Vitor H. M.; Assis, Ítalo A. S.; Xavier-de-Souza, Samuel (Anais da Escola Regional de Alto Desempenho da Região Nordeste (ERAD-NE), 2025)
This study proposes a method to reduce computational cost in time-domain wave modeling. By applying spherical geometric modeling, the wave equation is solved only in dynamically defined regions. The approach was evaluated using mean squared error (MSE) on 3D acoustic models with varying source positions and propagation times. Results showed up to 25% runtime reduction, highlighting the method’s potential for seismic imaging and reservoir analysis.